The Portrayal of American Indian Identity in The Lone Ranger and Tonto Fistfight in Heaven - Firdaus, Ahmad Fanan (English Literature Study Program, 2023)
This study delved into the cultural identity of American Indians residing in the Spokane reservation area, with a focus on Sherman Alexie's collection of stories,